Tantangan dan Strategi Pembelajaran Biologi di SMAN dalam Pelaksanaan Kurikulum Merdeka - Manjillatul Urba; Yesaya Haria; Innes Prameswary; Ade Suryanda; Daniar Setyo Rini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The curriculum is a very important part in organizing learning. The curriculum in Indonesia itself has undergone many changes to adapt learning to current developments. The independent curriculum, as a new curriculum in education, focuses on increasing effectiveness and flexibility compared to the previous curriculum, which allows learning to be adjusted according to the interests, talents, potential and needs of each student. This research aims to identify challenges and useful strategies in teaching biology using the independent curriculum. The research method involves direct observation and interviews with biology teachers. The research results show that there are several challenges for biology teachers, such as differences in student abilities, lack of active participation in class, and too many students in one class. To overcome this, teachers can use strategies such as assessing students' abilities not only through tests, providing initial worksheets to assess students' abilities, presenting important material if class time is limited, and utilizing existing educational technology. Therefore, teachers have a very important role in achieving learning goals in the independent curriculum